2023
DOI: 10.9778/cmajo.20220198
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in pragmatic trials: online survey of corresponding authors of published trials

Shelley Vanderhout,
Pascale Nevins,
Stuart G. Nicholls
et al.

Abstract: I n recent years, there has been increasing interest in conducting randomized controlled trials (RCTs) that are pragmatic in orientation. 1,2 Pragmatic trials use study settings and methods similar to usual care, as well as taking into account the perspectives of patients. 3,4 Some of the design features of pragmatic trial design -for example, selecting outcomes that are important to patients 5 -overlap with objectives of patient-oriented research. [6][7][8] Patient and public involvement (PPI) in research pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…( 22) Despite reported bene ts of consumer involvement, (23,24,25) many clinical trialists do not involve consumers in their research. (22,26) There are several areas of uncertainty around 'involving' consumers in research, which may explain why this topic was so highly ranked in our study. Barriers to researchers involving consumers in trials include a perceived lack of requirement to involve consumers, lack of knowledge on how to involve consumers effectively and systematically, and lack of infrastructure or resources to do so.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…( 22) Despite reported bene ts of consumer involvement, (23,24,25) many clinical trialists do not involve consumers in their research. (22,26) There are several areas of uncertainty around 'involving' consumers in research, which may explain why this topic was so highly ranked in our study. Barriers to researchers involving consumers in trials include a perceived lack of requirement to involve consumers, lack of knowledge on how to involve consumers effectively and systematically, and lack of infrastructure or resources to do so.…”
Section: Discussionmentioning
confidence: 93%
“…Barriers to researchers involving consumers in trials include a perceived lack of requirement to involve consumers, lack of knowledge on how to involve consumers effectively and systematically, and lack of infrastructure or resources to do so. (22,27) A recent survey of clinical trial networks in Australia found that only 27% of research organisations provided speci c training to their employees on consumer involvement in research, and very few had an established policy or process for involving consumers in clinical trials. (27) Similarly, a survey of musculoskeletal researchers in Aotearoa New Zealand found that only 1 in 10 studies involve consumer partners.…”
Section: Discussionmentioning
confidence: 99%
“…We recognise the challenges with attaining and sustaining the engagement of members of populations yet advise engaging interest holders, particularly representatives of populations experiencing inequities. It is also a possibility that the engagement of interest holders might have been underreported [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third highest ranked learning need by panellists was “Involving consumers from musculoskeletal trial design through to dissemination”, reflecting growing recognition of the importance of involving consumers in research [ 27 ]. The most common reasons that researchers involve consumers within their trials is to increase research relevance and trial quality [ 28 ]. Despite reported benefits of consumer involvement, [ 29 31 ] many clinical trialists do not involve consumers in their research [ 28 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common reasons that researchers involve consumers within their trials is to increase research relevance and trial quality [ 28 ]. Despite reported benefits of consumer involvement, [ 29 31 ] many clinical trialists do not involve consumers in their research [ 28 , 32 ]. There are several areas of uncertainty around ‘involving’ consumers in research, which may explain why this topic was so highly ranked in our study.…”
Section: Discussionmentioning
confidence: 99%